LAYANAN BIMBINGAN KARIER SECARA DARING TERHADAP KEMANDIRIAN KARIER SISWA - Maman Maman; Asep Samsudin; Ardian Renata Manuardi (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2022)
Online Career Guidance Services Using Google Class Room and Google Meet for Student Career Independence at YUPPI Soreang Madrasah Aliyah 2020/2021 Academic Year. This study aims to find out how the Implementation, Response and Barriers of Career Guidance services using the Google Class Room and Google Meet applications towards the career independence of students at Madrasah Aliyah YUPPI Soreang Academic Year 2020/2021. The counselee's independence development service which is the basis of the service, guides students in developing the counselee's talents and abilities. The stage of service implementation is to prepare services and mediap applications that will be used in service delivery. Conducted in the form of a service that uses a reality approach, data collection is carried out using qualitative descriptive research. Conducted in 5 meetings, covering four stages of implementation consisting of planning, action, observation, and reflection. The research was conducted at Madasah Aliyah YUPPI Soreang. The results showed an increase in changes in student behavior activities to become more independent. These results show that online Career Guidance Services using Google Classroom and Google Meet towards student career independence at MA YUPPI Soreang for the 2020/2021 Academic Year have become more independent than before.Keywords: Career Guidance, GoogleClassroom and Meet Applications, Career Independence